Investigating the influence of mineral content changes on mechanical properties through ligament insertion - Gouissem, Afif; Alkhatib, Fadi; Adouni, Malek (Frontiers in Aging, 2025)
IntroductionThis study investigates the relationship between mineral content and mechanical properties in collagenous tissues using a mesoscopic model. Unlike previous studies that assumed uniform mineral distributions, our model mimics the impact of combined intrafibrillar and extrafibrillar progressive mineralization on the ligament insertion using a realistic mineral gradient. To our knowledge, this is the first study on a minerally graded region that combines both mineral phases within a mesoscopic Molecular Dynamics framework.MethodsA collagen fibril model is constructed, and Molecular Dynamics (MD) simulations are performed at five equidistant locations along the insertion to analyze the influence of mineralization on collagen fibrils. The model captures the real randomness in mineral cluster size and distribution, improving its accuracy.ResultsResults show that while Young's modulus and ultimate tensile strain remain relatively unchanged, ultimate tensile strength, yield strain, and yield strength are significantly affected by the presence of the mineral content. These changes are mainly caused by the interatomic bonds that restrain the collagen molecular sliding within the fibril.DiscussionClinically, this research sheds light on the mechanical role that the progressive mineral gradient plays in load transfer and stress distribution. It also lays the ground for exploring the effects of aging and other pathological conditions such as ectopic mineralization or calcific tendinopathy, which alter the natural mineral gradient and increase the risk of tissue failure.